UBE2J1 is identified as a novel plasma cell-related gene involved in the prognosis of high-grade serous ovarian cancer - Yunjie Tian; Ruoyu Dong; Yingxia Guan; Ying Wang; Wei Zhao; Jun Zhang; Shan Kang (Journal of Translational Medicine)
Abstract Background Immune cells within tumor tissues play important roles in remodeling the tumor microenvironment, thus affecting tumor progression and the therapeutic response. The current study was designed to identify key markers of plasma cells and explore their role in high-grade serous ovarian cancer (HGSOC). Methods We utilized single-cell sequencing data from the Gene Expression Omnibus (GEO) database to identify key immune cell types within HGSOC tissues and to extract related markers via the Seurat package. The effects of immune cell markers on prognosis were analyzed via univariate Cox regression, least absolute shrinkage and selection operator (LASSO) and gene set variation analysis (GSVA) of bulk sequencing data from The Cancer Genome Atlas (TCGA)-HGSOC cohort. Finally, the effects of key markers on HGSOC cells were evaluated via Cell Counting Kit-8 (CCK-8), Transwell, colony formation, wound healing, immunofluorescence and in vivo tumor growth assays. Results At the single-cell level, we detected a significant increase in the proportion of plasma cells in HGSOC samples compared to that in normal ovarian samples. Within HGSOC tissues, these plasma cells were found to interact with CD8 + T cells, fibroblasts and endothelial cells. In addition, patients in the high-plasma cell-related score group had better survival rates and higher epithelial‒mesenchymal transition (EMT), apoptosis and immune scores. Moreover, univariate Cox and LASSO regression analyses revealed that ubiquitin-conjugating enzyme E2 J1 (UBE2J1) is a prognostic marker in HGSOC. Further functional studies revealed that overexpression of UBE2J1 promoted cell proliferation, invasion, migration and colony formation, whereas UBE2J1 knockdown attenuated the abovementioned cellular behaviors. Additionally, UBE2J1 overexpression promoted EMT, as evidenced by alterations in the protein expression levels of N-cadherin, snail family transcriptional repressor 2 (Slug), Twist family BHLH transcription factor 1 (Twist 1) and E-cadherin. Moreover, we found that UBE2J1 silencing was able to inhibit the tumor growth in vivo. Conclusions Overall, this study elucidated the role of plasma cells and revealed UBE2J1 as a novel oncogene in HGSOC, uncovering new mechanisms related to HGSOC tumorigenesis and promising therapeutic targets for HGSOC patients.